Wittgenstein and the foundations of bioethics: reflections on scientific and religious thinking in modernity - Vest, Matthew (2018)
This thesis argues that bioethics emerged in the late 1960s and early 1970s not as a novel way to engage new technological or social ethical questions of life (bios), but rather as a late, post-Enlightenment secular phenomenon. In particular, bioethics seeks to adopt a methodology of theorizing on morality that is prominent in modern science, and this is a strategy that I contest by following Wittgenstein’s critique of scientific theorizing. Wittgenstein’s later exercises with language present a critical and clarifying way to identify the immanent and self-referential schema of principlism in bioethics. Additionally, I show how Wittgenstein’s approach to philosophy as a skillful and therapeutic activity rather than a cognitive content is informative for bioethics. Hence, I suggest that in pre-modern, traditional eras—or even in many contemporary non-Western global sectors—bioethics largely would be indistinct from religious and theological dogma and practices. I argue that the modern mind prioritizes material causality, leading to a moral techne that divides spirit from matter, vios from bios. Within such a schema, nature—and especially the medicalized human body—is managed, produced, and constructed. Furthermore, I argue that Wittgenstein gestures towards an ancient transcendent way beyond the modern division of vios and bios, and that a full vision of seeing life may be glimpsed through an apophatic epistemology that guides one towards an understanding of ethics itself as a form of apophatic and embodied knowledge.